Conical epidermal cells cause velvety colouration and enhanced patterning in Mandevilla flowers. (28th July 2020) - Stavenga, Doekele G.; Staal, Marten; van der Kooi, Casper J.
Abstract : Conical epidermal cells of Mandevilla sanderi flowers enhance colour contrast by decreasing surface gloss and increasing long-wavelength reflectance. Abstract : The majority of angiosperms have flowers with conical epidermal cells, which are assumed to have various functions, such as enhancing the visual signal to pollinators, but detailed optical studies on how conical epidermal cells determine the flower's visual appearance are scarce. Here we report that conical epidermal cells of Mandevilla sanderi flowers effectively reduce surface gloss and create a velvety appearance. Owing to the reduction in surface gloss, the flower further makes more efficient use of floral pigments and light scattering structures inside the flower. The interior backscattering yields a cosine angular dependence of reflected light, meaning that the flowers approximate near-perfect (Lambertian) diffusers, creating a visual signal that is visible across a wide angular space. Together with the large flowers and the tilted corolla tips, this generates a distinct visual pattern, which may enhance the visibility to pollinators.